FINDING THE "RIGHT" SCIENCE PROGRAM. - Thomas, R. Murray (Elementary School Journal, 1952)
The article focuses on developing the right science curriculum for students in the U.S. In most schools, there is no definite focus in teaching science subjects. Teachers often have a hard time determining what to teach the students because there is no such thing as right science. What is right depends on how much science have the students learned before, what fields of science were taught to them and what the school's science course study should be taught in that grade. Overall, a right science program is the continuity and consistency of what is taught from grade to grade.